De cómo un conflicto parroquial influyó en los debates sobre la laicidad argentina: la destitución del cura de San Cristóbal en 1886 y sus inesperadas derivaciones - Di Stefano, Roberto (Pontificia Universidad Católica del Perú, 2022)
In Argentine history, the 1880s are famous for the public debate around the definition of secularism. In that decade, three legislative projects were discussed and promulgated, giving form to the «secular laws» of education, civil registration, and civil marriage. In 1886, a trivial conflict between a parish priest from the suburbs of Buenos Aires and the archbishop fueled a confrontation that reached the highest political and ecclesiastical spheres, attracted the attention of leading public figures, and even led to the adoption of relevant legislation measures. The story of that episode is interesting because it put on the table crucial issues that defined secularism; shows how a fortuitous event, initially inconsequential, can acquire importance in decision-making at the highest level; illustrates the intricate relationships that mediate between events, conjunctures, and structural transformations; and informs about the dialectical links between discourses and their contexts of enunciation.

En la historia argentina, la década de 1880 es célebre por los debates públicos en torno a la definición de la laicidad. En ese decenio se discutieron y promulgaron tres proyectos legislativos que se cristalizaron en las «leyes laicas» de educación, registro civil y matrimonio civil. En 1886, un conflicto aparentemente baladí entre un párroco de los suburbios de Buenos Aires y el arzobispo potenció un enfrentamiento que alcanzó las más altas esferas políticas y eclesiásticas, concitó la atención de personajes públicos de primera línea y hasta dio lugar a la adopción de medidas legislativas relevantes. La historia de ese episodio es interesante porque puso sobre el tapete temas cruciales que hacían a la definición de la laicidad y porque muestra el peso que un hecho fortuito, en principio intrascendente, puede adquirir en la toma de decisiones al más alto nivel, ilustra las intrincadas relaciones que median entre acontecimientos, coyunturas y transformaciones estructurales y nos habla de los vínculos dialécticos entre los discursos y sus contextos de enunciación.
How a parish conflict influenced the debate on Argentine secularism: the dismissal of the priest of San Cristóbal in 1886 and its unexpected implications
Keywords: Argentine; 19th century; Secularism; Patronage; Argentina; Siglo XIX; Laicidad; Patronato; https://purl.org/pe-repo/ocde/ford#6.01.01